PERENCANAAN PEMBANGUNAN DAERAH OTONOMI KHUSUS (STUDI TRANSPORTASI DARAT DAN LAUT MENUJU DISTRIK ENCLAVE OE-CUSSE AMBENO, TIMOR-LESTE) - Francelino Sarmento Martins (Universitas Tribhuwana Tunggadewi, 2015)
Abstract : The lack of transportation facilities and infrastructure for the district of Oe-Cusse Ambeno, which is an enclave located in the middle of the region of Indonesian Republic, an area which is directly adjacent to several area of NTT (East Nusa Tenggara).The limitation or the lack of land, sea, and air means of transportation is a very alarming situation since East Timor became the Democratic Republic of Timor-Leste. The findings show that the lack of transportation facilities and infrastructure is due to the fact that the government still faces several constraints related to land transportation connecting Oe-Cusse with the capital of Democratic Republic of Timor-Leste. There are several factors that affect the role of government in planning the development of transportation namely; 1) supporting factors: a) the increasing number of transportaion service users , b) the demands of public transportation service by Oe-Cusse Ambeno people, c) The existence of a new status of Oe-Cusse Ambeno as a Special Administrative Region and the Special Economic Zone of Social and Trade , d) Oe-Cusse Ambeno is considered as both enclave and border areas. 2) hindering factors; a) political and security factors, b) the absence of maximum cooperation between the two countries (Democratic Republic of Timor-Leste -Indonesian Republic) in transportation sector, c) the border issue between the two countries is still debatable and d) the administration is still centralized.